2009
DOI: 10.1074/jbc.m902074200
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Roles of Peroxisome Proliferator-activated Receptor α and Growth Hormone in the Regulation of CYP4A11 Expression in a Transgenic Mouse Model

Abstract: CYP4A11 transgenic mice (CYP4A11 Tg) were generated to examine in vivo regulation of the human CYP4A11 gene. Expression of CYP4A11 in mice yields liver and kidney P450 4A11 levels similar to those found in the corresponding human tissues and leads to an increased microsomal capacity for -hydroxylation of lauric acid. Fasted CYP4A11 Tg mice exhibit 2-3-fold increases in hepatic CYP4A11 mRNA and protein, and this response is absent in peroxisome proliferator-activated receptor ␣ (PPAR␣) null mice. Dietary admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…The decreased PPAR␣ expression strongly correlated with the reduced expression levels of Cyp2d22 and Cyp2e1 ( Table 2), suggesting that PPAR␣ potentially participates in regulation of P450 expression during mouse pregnancy. In fact, it has been shown that a peroxisome proliferator activator (such as WY-14,643) down-regulates CYP2C11 and CYP2C12 while up-regulating CYP4A in rats (Corton et al, 1998;Graham and Lake, 2008) and mice (Savas et al, 2009). However, it is uncertain whether these results can be extrapolated to humans.…”
Section: Discussionmentioning
confidence: 90%
“…The decreased PPAR␣ expression strongly correlated with the reduced expression levels of Cyp2d22 and Cyp2e1 ( Table 2), suggesting that PPAR␣ potentially participates in regulation of P450 expression during mouse pregnancy. In fact, it has been shown that a peroxisome proliferator activator (such as WY-14,643) down-regulates CYP2C11 and CYP2C12 while up-regulating CYP4A in rats (Corton et al, 1998;Graham and Lake, 2008) and mice (Savas et al, 2009). However, it is uncertain whether these results can be extrapolated to humans.…”
Section: Discussionmentioning
confidence: 90%
“…The cross-reactivity of the resultant antibody with P450 4F11 and 4F12 was then removed by back-adsorption of anti-P450 4F2 IgG against a Affi-Gel 10 agarose gel solid-phase support to which P450 4F11 and 4F12 Sf9 lysate proteins had been coupled. We previously used a similar procedure to remove the cross-reactivity of murine CYP4A proteins with antibodies to human P450 4A11 (Savas et al, 2009). The final back-absorbed antibody exhibited cross-reactivity with P450 4F2 and P450 4F3 and was designated as anti-P450 4F2/3 IgG (Supplemental Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The RNA concentration was determined spectrophotomically. The primers used for measurement of Cyp4a12, Cyp4a14, L27, and PPAR␣ mRNA were described previously (Savas et al, 2009). The sequences for all other primers used for qPCR are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%